Variable coordination modes of an active ligand periphery in 1,3-bis(2-pyridylimino)isoindolato copper(II) complexes - Sauer, Désirée C.; Wadepohl, Hubert (Polyhedron, 2014)
Copper(II) complexes of a new family of chiral tridentate 1,3-bis(2-pyridylimino)isoindoline (BPIH) ligands bearing peripheral, potentially ligating ether groups have been prepared and structurally characterized by X-ray diffraction and EPR spectroscopy. The acetato, halogenido, and triflato complexes display different degrees of coordination of the ligand periphery in the complex structure, and the complex geometry varies by coordination of the oxygen atoms of the ether moieties of the ligand side arms. Furthermore, the BPIs may act as monoanionic or neutral ligands depending on the protonation status of the isoindoline ligand backbone. Formation of complexes with deprotonated or protonated ligands may be controlled by the presence or absence of a base during the complexation reaction.